2016
DOI: 10.1126/scitranslmed.aag1370
|View full text |Cite
|
Sign up to set email alerts
|

Allergic asthma is distinguished by sensitivity of allergen-specific CD4 + T cells and airway structural cells to type 2 inflammation

Abstract: Despite systemic sensitization, not all allergic individuals develop asthma symptoms upon airborne allergen exposure. Determination of the factors that lead to the asthma phenotype in allergic individuals could guide treatment and identify novel therapeutic targets. In this study, we utilized segmental allergen challenge (SAC) of allergic asthmatics (AA) and allergic non-asthmatic controls (AC) to determine if there are differences in the airway immune response or airway structural cells that could drive the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…Previously [26], as in this work, we reported on the correlation between mucus pixel intensity in OCT and mucin content, and found them to be reasonably well correlated (p = 0.03 for the 30 subjects included in this analysis). Although pixel intensity has been used to characterize fluid particulate in other OCT applications [30], it is nevertheless not ideal in analyzing mucus due to the fact that dense and heterogeneous distributions of mucus can cause strong scattering effects that can impact the accuracy of the measurements.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Previously [26], as in this work, we reported on the correlation between mucus pixel intensity in OCT and mucin content, and found them to be reasonably well correlated (p = 0.03 for the 30 subjects included in this analysis). Although pixel intensity has been used to characterize fluid particulate in other OCT applications [30], it is nevertheless not ideal in analyzing mucus due to the fact that dense and heterogeneous distributions of mucus can cause strong scattering effects that can impact the accuracy of the measurements.…”
Section: Discussionsupporting
confidence: 76%
“…To evaluate our segmentation and mucus classification algorithms in human in vivo data sets, we analyzed data sets that had previously been obtained in a clinical study involving 18 allergic asthmatic and 22 allergic non-asthmatic subjects [26]. The clinical characteristics of the subjects and the details of this study, which involved a titrated allergen challenge, have been described elsewhere [26][27][28][29].…”
Section: Clinical Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…All HC subjects had a negative reaction to skin test. Asthmatics were classified as previously described . All asthmatic volunteers had a PC20 (concentration of methacholine needed to produce a 20% fall of FEV 1 from baseline) of less than 20 mg/mL at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…One study that sampled the airways of adults with allergic asthma identified low numbers of allergen‐specific CD4 + T cells by tetramer staining that were enriched for cells that co‐expressed receptors for the alarmins IL‐33 (ST2), and IL‐25, and prostaglandin D2 (CRTH2). Receptor expression was enhanced after segmental allergen challenge . The same study reported a correlation between ST2 expression on allergen‐specific T cells and Th2 cytokine levels in BAL fluid, which would be consistent with IL‐33‐mediated triggering.…”
Section: T Cells and Severe Asthma: Current Conceptsmentioning
confidence: 99%